Cevaplar

2012-11-29T20:36:16+02:00
2x3 – 5x2 – 3x + 2 = 2 please solve, ten points, in a rush thank you!! (:? x3 + 64 = 0
x4 – 8x2 – 9 = 0 3 years ago Report Abuse Oliver Kahn Best Answer - Chosen by Voters 1)
2x² – 5x² – 3x + 2 = 2

2x² – 5x² – 3x = 0

x(2x - 5x - 3) = 0

x= [5 ± √(25+24)]/4 = (5 ± 7)/4

x1 = 3
x2 = -1/2

so:

x(x+1/2)(x-3)

x(2x+1)(x-3)

2)
x³ + 64 = 0

64 = 4³

(x+4)(x²+4x+16)

3)

x^4 - 8x² - 9 = 0

x² = t

t² - 8t - 9 = 0

t = [8 ± √(64+36)]/2 =  Search Yahoo! for Search Action Bar: stars - mark this asInteresting! Email Comment (0) Save   Other Answers (5) kindrick... 2x3 – 5x2 – 3x + 2 = 2

2x3 – 5x2 – 3x = 0

x(2x^2 - 5x - 3) = 0

In the trinomial ac = 2(-3) = -6

Factors of -6 that add to -5 are +1 & -6

x(2x^2 + x - 6x - 3) = 0

x[x(2x + 1) - 3(2x + 1)] = 0

x(x - 3)(2x + 1) = 0

x = 0, 3, -1/2 3 years ago Report Abuse 0% 0 Votes Shahd 1) 2x3 – 5x2 – 3x + 2 = 2 
x (2x^2 -5x -3) +2-2 =0

x = 0
x = 3
x = -1/2

2) x3 + 64 = 0
x^3 = -64
x = -4

3) x4 – 8x2 – 9 = 0
(x^2 - 9) (x^2+1)
x = 3, x = -3 3 years ago Report Abuse 0% 0 Votes fizixx 1) zero, 3, and -1/2

2) -4, 2 ± 2i√3

3) ±3, ±i 3 years ago 0% 0 Votes   2x(3)-5x(2)-3x+2=2
-6x(3)(2)+2=2
-6x(6)+2=2
-36x=0
x=0
0